Evaluation is an attitude - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
With 'capacity development' at the core of many organisations priorities, the need for proper and ongoing evaluation is becoming more widely understood. This sensitive area involves people and makes judgements about their work and achievements. It...